College algebra (a simplified approach): book I - Buquing, Sancho Sumbad; Bhagnawi, Ernie T. (Quezon City, 2004)
This book consists of the following topics : the number system of algebra, algebraic expressions, operations and factoring of polynomials, linear equations and functions and graphs
Keywords: algebra